BOLD Signal in memory paradigms in hippocampal region depends on echo time. Issue 5 (2nd November 2012) - Milian, Monika; Zeltner, Lena; Klamer, Silke; Klose, Uwe; Rona, Sabine; Erb, Michael
Abstract Purpose: To evaluate the hypothesis that the entire hippocampus might be affected by susceptibility artifacts. Previous studies described susceptibility artifacts in the amygdala and the anterior hippocampus. Materials and Methods: We investigated 20 subjects with a verbal memory paradigm aiming at testing two different TEs (45 vs. 64 msec) at 1.5 T for hippocampal blood oxygenation level‐dependent (BOLD) activity. T2* maps were calculated from the normalized mean echo‐planar imaging (EPI) of the two echo times (TEs). Results: Within the hippocampal region of interest (ROI), the amount of suprathreshold voxels was significantly higher at TE = 64 msec compared to TE = 45 msec. When corrected for multiple comparisons (family‐wise error [FWE] in a small volume of interest, P < 0.05) we no longer found significant activations at TE = 45 msec, while a significant number of voxels remained after the small volume correction (P < 0.05, FWE) within the ROI at TE = 64 msec. Conclusion: Although a shorter TE demonstrates advantages, a TE of 45 msec leads to a significant loss of BOLD signal detection in memory functional magnetic resonance imaging (fMRI) studies when compared to 64 msec. We assume that the hippocampal region, even the anterior part, is not strongly affected by susceptibility gradients. J. Magn. Reson. Imaging 2013;37:1064–1071. © 2012 Wiley Periodicals, Inc.